EFFECT OF ROCKET LEAVE JUICE (ERUCA SATIVA) JUICE ON CHROMOSOMAL ABERRATIONS OF WHITE MICE BONE MARROW CELLS - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
The effect of the rocket juice Eruca sativa (A cruciferous plant ) and its counter effect on chromosomal aberrations induced by Cyclophosphamide (Cp) drug was studied in white mice bone marrow cells .The effect of different combinations of plant juice and mutagen was studied to find out the patterns of protection exert on the aberrations . Results revealed that rocket juice 0.1 , 0.25 , 0.5 / ml animal administrated orally had no effect on induction of chromosomal aberrations , while Cp administrated orally (50 mg / Kg of body weight) , increased the chromosomal aberrations 7 – 11 times of the natural level (Negative control) . Natural repair and activities failed to restore the natural levels as the aberrations still very high .The structural chromosomal aberrations (Chromosome breaks , chromatid breaks , ring chromosomes , and dicentric chromosomes ) induced by Cp were lowered upon using the juice before or after or with the mutagen with significant difference . The prevention (Protection) was proportional to time intervals of treatments , and reached its maximum value (91 % ) when treatment with juice before treatment with mutagen was conducted for 6 days .